PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2022 - Feby Zasa; Noor Hidayati; Siti Rusidah; Maryono (Business Administration, FISIP ULM, 2023)
Despite experiencing negative growth during the Covid-19 pandemic in 2020, the national economy has shown resilience and a faster recovery. The stock prices of the mining sector have witnessed significant fluctuations during the period 2017-2022. This research aims to understand and examine the influence of Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS). The research is quantitative research with focuses on mining companies within the largest market capitalization companies according to the Indonesia Stock Exchange in 2022. Financial reports of mining companies serve as the population, with 30 financial reports selected as samples from 5 mining companies based on specific criteria. The results indicate that Return on Assets (ROA) does not have a significant partial effect on stock prices, Return on Equity (ROE) does not have a significant partial effect on stock prices, and Earnings Per Share (EPS) has a significant partial effect on stock prices.